Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar PAK Pada Peserta Didik Kelas VIII SMP GKST 3 Tentena - Ipan Morris Pangaribuan; Robinhot Sirumapea (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Christian Religious Education plays a vital role in shaping the character, spirituality and moral values of learners in the modern educational era. A learning process that remains teacher-centred results in low student participation and poor learning outcomes in terms of understanding Christian values. This situation highlights the need for an interactive cooperative learning model to optimally enhance learners’ engagement, understanding and learning outcomes. This study aims to analyse the application of the Numbered Heads Together (NHT) cooperative learning model in improving student learning outcomes. The research employs a descriptive qualitative method through literature review and field observation to analyse the implementation of the NHT learning model. The results indicate that the NHT model enhances student participation, cooperation, and understanding of Christian Religious Education material. Further results indicate a significant improvement in students’ learning outcomes, motivation, sense of responsibility, and critical thinking skills. The NHT learning model is capable of creating an active, collaborative learning environment focused on fostering students’ Christian character. The application of NHT also strengthens social interaction, individual responsibility, and students’ communication skills within the learning process. The NHT model is relevant for application in modern Christian Religious Education as it supports contextual, reflective, and transformative learning on an ongoing basis. Abstrak Pendidikan Agama Kristen memiliki peran penting dalam membentuk karakter, spiritualitas, dan moral peserta didik di era pendidikan modern. Proses pembelajaran yang masih berpusat pada guru menyebabkan rendahnya partisipasi serta hasil belajar siswa dalam memahami nilai-nilai iman Kristen. Kondisi tersebut menunjukkan perlunya model pembelajaran kooperatif yang interaktif untuk meningkatkan keterlibatan, pemahaman, dan hasil belajar peserta didik secara optimal. Penelitian ini bertujuan menganalisis penerapan model pembelajaran kooperatif tipe Numbered Heads Together dalam meningkatkan hasil belajar siswa. Penelitian menggunakan metode kualitatif deskriptif melalui studi pustaka dan observasi lapangan untuk menganalisis implementasi model pembelajaran NHT. Hasil penelitian menunjukkan model NHT meningkatkan partisipasi, kerja sama, serta pemahaman siswa terhadap materi Pendidikan Agama Kristen. Hasil lainnya menunjukkan peningkatan hasil belajar, motivasi, tanggung jawab, dan kemampuan berpikir kritis peserta didik secara signifikan. Model pembelajaran NHT mampu menciptakan suasana belajar yang aktif, kolaboratif, dan berorientasi pada pembentukan karakter Kristiani siswa. Penerapan NHT juga memperkuat interaksi sosial, tanggung jawab individu, serta kemampuan komunikasi peserta didik dalam proses pembelajaran. Model NHT relevan diterapkan dalam Pendidikan Agama Kristen modern karena mendukung pembelajaran kontekstual, reflektif, dan transformatif secara berkelanjutan.